2023
DOI: 10.1111/petr.14456
|View full text |Cite
|
Sign up to set email alerts
|

The Fontan immunophenotype and post‐transplant outcomes in children: A multi‐institutional study

Abstract: Background Patients after Fontan palliation represent a growing pediatric population requiring heart transplant (HTx) and often have lymphopenia (L) and/or hypogammaglobinemia that may be exacerbated by protein‐losing enteropathy (PLE, P). The post‐HTx effects of this altered immune phenotype are not well studied. Methods In this study of the Pediatric Heart Transplant Society Registry, 106 Fontan patients who underwent HTx between 2005 and 2018 were analyzed. The impact of lymphopenia and PLE on graft surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…These studies highlight well a fundamental challenge that remains a critical element in the care of the post-transplant Fontan patient: how do we tailor immunosuppression to minimize both posttransplant infection and rejection in these children with such altered pretransplant immunophenotypes? In a group in which similar induction immunosuppression was used, infections predominated in those with PLE and/or lymphopenia 5 ; in a group with more frequent use of lower intensity immunosuppression (basiliximab vs. ATG) in the setting of PLE, AMR predominated. 6 Perhaps a more nuanced and individualized risk evaluation of both infection and rejection in these patients, in whom traditional measures may be unsatisfactory, may help guide us toward improved overall outcomes.…”
Section: Two Sides Of the Same Coin: Balancing The Risks Of Rejection...mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight well a fundamental challenge that remains a critical element in the care of the post-transplant Fontan patient: how do we tailor immunosuppression to minimize both posttransplant infection and rejection in these children with such altered pretransplant immunophenotypes? In a group in which similar induction immunosuppression was used, infections predominated in those with PLE and/or lymphopenia 5 ; in a group with more frequent use of lower intensity immunosuppression (basiliximab vs. ATG) in the setting of PLE, AMR predominated. 6 Perhaps a more nuanced and individualized risk evaluation of both infection and rejection in these patients, in whom traditional measures may be unsatisfactory, may help guide us toward improved overall outcomes.…”
Section: Two Sides Of the Same Coin: Balancing The Risks Of Rejection...mentioning
confidence: 99%
“…Mantell et al 5 leveraged detailed laboratory and diagnostic data within the Pediatric Heart Transplant Society database to characterize the pretransplant immunophenotype of 106 children with failing Fontan physiology who underwent heart transplant. The four immunophenotypes were those with lymphopenia and PLE (L+ P+), lymphopenia without PLE (L+ P−), no lymphopenia and PLE (L− P+), and neither lymphopenia nor PLE (L− P−).…”
mentioning
confidence: 99%
“…Nonetheless, many controversies still exist including timing of referral to advanced heart failure teams, indication for and timing of advanced heart failure therapies, indications and contraindications for transplantation, timing of listing for transplantation, the impact of renal and hepatic dysfunction on these decisions and on post‐transplant outcomes, and the role of combined heart‐liver transplantation, just to name a few. These are further clouded by Fontan‐related co‐morbidities that do not manifest as heart failure including protein‐losing enteropathy and plastic bronchitis 52,53 . Given the increasing post‐transplant survival and the burgeoning population of adult CHD patients with Fontan circulations, this is an evolving challenge for advanced heart failure and heart transplant teams.…”
Section: 'S—the Challenge Of Transplant For Congenital Heart Disease ...mentioning
confidence: 99%
“…These are further clouded by Fontan-related comorbidities that do not manifest as heart failure including proteinlosing enteropathy and plastic bronchitis. 52,53 Given the increasing post-transplant survival and the burgeoning population of adult CHD patients with Fontan circulations, this is an evolving challenge for advanced heart failure and heart transplant teams. However, over half of all pediatric heart candidates are sensitized with anti-HLA antibodies.…”
Section: Recipients With Prior Fontan Procedures (And Its Variants)mentioning
confidence: 99%
“…A recent analysis of the Pediatric Heart Transplant Study found that Fontan patients with lymphopenia and/or proteinlosing enteropathy had higher rates of infection post-HT compared to patients with neither at time of heart transplant (22.1 vs. 41.4%) with no corresponding difference in rejection, malignancy, or graft survival at 1 year. 3 However, this analysis was limited by varying induction regimens and limited granularity typical of registry analysis.…”
Section: In the Article "Increased Risk Of Infections In Pediatric Fo...mentioning
confidence: 99%